Bioactivity of selected plant-derived essential oils against Zabrotes subfasciatus (Coleoptera: Bruchidae) - Bernardes, Wagner A. [UNESP]; Silva, Eliane O.; Crotti, Antonio E. M.; Baldin, Edson L. L. [UNESP] (Elsevier B.V., 2018)
The common bean Phaseolus vulgaris L (Fabaceae) is an important vegetable protein source and constitutes a significant part of the diet in many tropical countries. The Mexican bean weevil Zabrotes subfasciatus (Boheman) (Coleoptera: Bruchidae) is one of the main pests affecting stored beans: it causes extensive qualitative and quantitative grain loss. We investigated the bioactivity of the essential oils extracted from Chenopodium ambrosioides L (CA-EO), Ocimum gratissimum L (OG-EO), and Schinus terebinthifolius Raddi (ST-EO) against Z. subfasciatus. After 12-h treatment, CA-EO and OG-EO at 20.0 mu L/L of air killed 100% Z subfasciatus, whereas ST-EO at 100.0 mu L/L of air afforded 100% 1 subfasciatus mortality after 24 h. CA-EO provided the lowest 24 h LD50 (0.8 mu L/L of air) and displayed efficient repellent activity against Z subfasciatus. Our results demonstrate that CA-EO is a potentially economical and environmentally friendly alternative to manage Z. subfasciatus in stored beans. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Phaseolus vulgaris; Repellent activity; Fumigant activity; Essential oil; Stored grain management